Crystal structure of bis(6-aminopyridine-2-carboxylato–k2O,N)-bis(N,N-dimethylformamide-k1 O)zinc(II), C18H24N6O6Zn - Hong Dong-feng; Ye Jia-Qi; Guo Wen-Bo (Zeitschrift für Kristallographie - New Crystal Structures, 2023)
C18H24N6O6Zn, monoclinic, P21/n (no. 14), a = 10.1669(6) Å, b = 8.0831(4) Å, c = 13.1012(8) Å, β = 91.221(5)° $91.221(5){}^{°}$ , Z = 2, V = 1076.41(11) Å3, R gt(F) = 0.0396, wR ref(F2) = 0.0987, T = 273 K.